Factors Forming E-Trust that Attract Interest in Buying Classic Model Watches - Rendy Sudirman; Ujang Enas (Politeknik Ganesha Medan, 2024)
This study aims to determine the development and changes in trends among consumers in the digital era through the analysis of buying interest in classic type watch consumers who are influenced by price, brand image, and product design through e-trust. The research method uses descriptive quantitative method with structural equation model analysis technique through survey method of purposive sampling technique on 135 respondents of classic watch fans in East Priangan area. The results showed that price has a negative effect on e-trust, brand image has a positive effect, as well as product design which has a positive effect on e-trust, and e-trust moderates the independent variables positively and significantly on purchase intention. Existing gaps due to the effect of price can be added to discount prices, promotions, and service times to identify gaps in further research.